Theatre Made of Circus (by the Example of „Jocko – Brasilian Monkey”, 1825) - Ciechowicz, Jan (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
What is the circus? The paper is an attempt to define the phenomenon. It refers among others to the Olimpic Circus dating back to the times of Mickiewicz. Next, the melodrama in 3 acts, Jocko, brasilian monkey (1825) is being analysed. It was a great stage hit of the 19th century, translated into Polish by Józef Damse. The Polish premiere was held in the National Theatre in Warsaw (1928), where the monkey’s role was played ‘brilliantly’ by a dancer Heinrich Springer. During a long career of the drama, Stanisław Krzesiński’s acting was also excellent, including the performance on the stage of Stary Theatre in Lublin (for J. Frołowicz’s benefit concert, probably in 1829). The name of the actor looking like a monkey was camouflaged on the poster under ‘three asterisks’.